Expanding the Boundaries of Informal Education Programs: An Investigation of the Role of Pre and Post-education Program Experiences and Dispositions on Youth STEM Learning - Falk, John H.; Meier, David D. (Frontiers in Education, 2021)
For generations educators have been supporting children and youth’s STEM learning through informal education programming. Such programming includes a wide variety of outdoor education programs, camp programs, and increasingly targeted STEM programs run afterschool, on weekends, and over the summer months. However, despite the positive impacts these programs have, there is a long-standing flaw in how most educators have approached the design and improvement of these programs—a flaw that permeates almost all informal STEM education efforts. Either explicitly or implicitly, the focus of educators has been exclusively on what happens during the program itself, with little, if any, attention paid to what happens before or after children and youth participate in their programs; presumably because it has been assumed that what happens before or after a program is outside of the educator’s control. This study was designed to explore the impacts pre- and post-program experiences and dispositions had on the learning outcomes – creativity, STEM interest and problem solving – of 196 “current” and 352 “previous” youth participants in a one week STEM and invention-focused, summer camp program. Results indicated that differences in both pre- and post-camp variables, e.g., parental support, sociability, motivations for attending, and the number of prior as well as subsequent STEM-related experiences, significantly correlated with positive learning outcomes. Discussed are implications of these findings for the design of future informal science education programming.